2009
DOI: 10.1038/leu.2009.6
|View full text |Cite
|
Sign up to set email alerts
|

Antiepileptic drugs reduce efficacy of methotrexate chemotherapy by downregulation of Reduced folate carrier transport activity

Abstract: Concurrent treatment with methotrexate (MTX) and antiepileptic drugs, such as phenobarbital (PB), reduces the efficacy of MTX chemotherapy in childhood acute lymphoblastic leukemia (ALL). This can result from defective Reduced folate carrier (Rfc1)-dependent cellular uptake of MTX. Indeed, we have shown that functional Rfc1 activity is significantly reduced by clinically relevant concentrations of the anticonvulsant drugs PB or carbamazepine in an adequate in vitro model. As PB is known to regulate carrier-ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 51 publications
(71 reference statements)
0
22
0
Order By: Relevance
“…Activation of protein kinase C␣ stimulated by antiepileptic drugs such as phenobarbital induced the internalization and subsequent proteasomal degradation of RFC. Consequently, the uptake of methotrexate in tumor cells decreased as demonstrated by drug resistance in acute lymphatic leukemia patients (Halwachs et al, 2009(Halwachs et al, , 2011.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of protein kinase C␣ stimulated by antiepileptic drugs such as phenobarbital induced the internalization and subsequent proteasomal degradation of RFC. Consequently, the uptake of methotrexate in tumor cells decreased as demonstrated by drug resistance in acute lymphatic leukemia patients (Halwachs et al, 2009(Halwachs et al, , 2011.…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that we have shown that clinically relevant concentrations of PB or CBZ cause significant down-regulation of hepatocellular Rfc1 uptake activity through activation of the CAR signaling pathway (Halwachs et al, 2007(Halwachs et al, , 2009). The nuclear receptor CAR is known to mediate regulation of carrier associated drug transport by PB or CBZ through modulation of target gene expression, including MTX efflux transporter Mrp2 (Xu et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…where K r is the elastic constant, r ij is the distance 2 between particles i and j, d is the equilibrium distance between adjacent monomers, K θ is the bending modulus, θ i − 1, i + 1 is the angle between the bonds of the polymer having the bead i as central monomer, LJ the LJ energy depth and σ the monomer diameter. The effect of temperature fluctuations on the dynamics of a chain polymer escaping from a metastable state is studied in a twodimensional (2D) domain.…”
Section: Polymer Dynamics Modelmentioning
confidence: 99%
“…These are based on a drug delivery mechanism that crucially depends on the translocation time of the chemotherapeutic molecule carriers. 1,2 The study of the transport dynamics of macromolecules across a nanopore is also important in the development of technologies that can be applied to improve DNA or RNA molecule sequencing techniques 3,4 or to develop nanostructure-based electrical biosensors. 5,6 First experiments on polymer translocation were carried out by detecting the passage of DNA molecules across an α-hemolysin (α-HL) protein channel, by measuring the reduction of the electrolyte ion current.…”
Section: Introductionmentioning
confidence: 99%